Mathematical Modeling as a Didactic Strategy: A Procedural Perspective of Academic and Scientific Training (Docentes 2.0 Journal, 2023)
Currently, on a global scale, mathematical models and more specifically, modeling, or mathematical modeling as well as digital tools are essential to determine the characteristics and behavior of hypothetical situations that are presented to society in general. The objective of this scientific article was to analyze the mathematical modeling of a teaching strategy from a procedural perspective of academic and scientific training. Its methodology was based on the postpositivist paradigm under the systematic method of literature review, with a qualitative approach, with a descriptive and cross-sectional bibliographic design. The instrument used was raised according to the guidelines established in the PRISMA statement, after establishing the inclusion and exclusion criteria, a total sample of 31 works were identified, which were registered in a synthesis matrix as a data collection instrument where the content analysis was disseminated. In addition, a bibliographic record was prepared as a systematization of the reviewed data. This allowed to obtain a broad perspective and a logical structure of information. In conclusion, the benefits of mathematical modeling include the representation of problems, decision making, formulas and mathematical contents that allow simulating complex processes, generating, verifying hypotheses, predicting, in addition, the activity to represent, manipulate, communicate real world objects. and suggest test experiments. A mathematical model must reflect the causal structure of the system under study and be able to predict the outcome accurately and efficiently.
Keywords: Modeling; mathematics; strategy; didactics; academic and scientific training